Union Wage Effect in Sweden: Evidence from the Interwar Period - Supporting Data and Code - Skoglund, William (Uppsala University, 2025)
This package contains data and scripts for reproducing the results of the article: Union Wage Effect in Sweden: Evidence from the Interwar Period. The main dataset includes a new database with information on workplaces during the interwar period, including worked hours, number of workers, and wages paid. The database is based on primary materials from the official Swedish wage statistics.

Det här paketet innehåller data och skript för att återskapa resultaten för artikeln: Union Wage Effect in Sweden: Evidence from the Interwar Period. Det huvudsakliga datasetet innehåller en ny databas med information om arbetsplatser under mellankrigstiden, inklusive arbetade timmar, antal arbetare och utbetalade löner. Databasen baseras på primärmaterial till den officiella svenska lönestatistiken.
Union Wage Effect in Sweden: Evidence from the Interwar Period - Supporting Data and Code
Keywords: WAGES; LÖNER; TRADE UNIONS; FACKFÖRENINGAR; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Labour relations/conflict; Förhållande/konflikter mellan arbetsmarknadens parter; Economic History; Ekonomisk historia; Labour and employment policy; Arbetsmarknads- och sysselsättningspolitik